2019
DOI: 10.1111/bjh.15757
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ELF1, a lymphoid ETS domain‐containing transcription factor, is recurrently lost in classical Hodgkin lymphoma

Abstract: Summary Loss of B cell‐specific transcription factors (TFs) and the resulting loss of B‐cell phenotype of Hodgkin and Reed‐Sternberg (HRS) cells is a hallmark of classical Hodgkin lymphoma (cHL). Here we have analysed two members of ETS domain containing TFs, ELF1 and ELF2, regarding (epi)genomic changes as well as gene and protein expression. We observed absence or lower levels of ELF1 protein in HRS cells of 31/35 (89%) cases compared to the bystander cells and significant (P < 0·01) downregulation of the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…49 Both transcription factors have also been indicated to be required for normal B cell development. 50,51 Furthermore, the EICE is a well-known binding motif for IRF8-PU.1, as well as IRF4-PU.1 complexes. 18,35,36 The expression of IRF4 is, like IRF8, restricted to hematopoietic cells and also implicated in the development of dendritic cells and B cells.…”
Section: Discussionmentioning
confidence: 99%
“…49 Both transcription factors have also been indicated to be required for normal B cell development. 50,51 Furthermore, the EICE is a well-known binding motif for IRF8-PU.1, as well as IRF4-PU.1 complexes. 18,35,36 The expression of IRF4 is, like IRF8, restricted to hematopoietic cells and also implicated in the development of dendritic cells and B cells.…”
Section: Discussionmentioning
confidence: 99%
“…GATA3, FOXP3 and EOMES), and members of ETS family (e.g. EBF1, ELF1, ETV6), [4][5][6] were down-regulated and might contribute to the differentiation defect of PDX and RLH cells (Figure 2B, group 3 and 4 TFs). These results were consistent with gene ontology analysis using all differentially expressed genes (DEGs) (PDX vs. normal cells, or RLH vs. normal cells), which indicated that DEGs enriched in PDX tumours were strongly associated with MAPK pathway that utilizes AP-1 families of TFs for signal transduction 7 (Figure 2C).…”
mentioning
confidence: 99%
“…More specifically, PU.1 has a proven role in the regulation of Igκ transcription and rearrangement, as does ELF1 in the activation of several B-cell specific tyrosine kinases in mice that are important for proper BCR signaling [34,35]. Both factors are recurrently attenuated in cHL [5,16]. However, TNFAIP3 is a ubiquitin-modifying enzyme that targets the RIP1 protein for degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these putatively upregulated genes also seem to be involved to some extent in the regulation of transcription (Table 1). In light of these results, we further focused on deregulated miRNAs and their putative interactions with B-cell specific transcription factors SPI1 and ELF-1 attenuated in cHL [5,16] and also the NF-kB inhibitor TNFAIP3 recurrently inactivated in this lymphoma [17]. We selected the putative hsa-miR-27a-5p:SPI1, hsa-miR-330-3p:ELF-1 (two miRNA binding sites were tested), hsa-miR-542-3p:ELF1, hsa-miR-450b-5p:ELF-1 and the hsa-miR-23a-3p:TNFAIP3 interactions for experimental testing (Table 2).…”
Section: Biological Processes Deregulated By Mirnas In Chlmentioning
confidence: 99%
See 1 more Smart Citation